GEOGRAPHICAL INFORMATION SYSTEM BASED COVID-19 VULNERABILITY MAPPING IN PONTIANAK REGENCY WEST KALIMANTAN - Ajun Purwanto; Yoga Prasetya Adi Nugraha (Universitas Sebelas Maret (UNS), 2023)
2020 was the start of the toughest year for the world community in general, especially Indonesia in the health sector. The outbreak of the Covid-19 case in various regions requires clear and accurate information in efforts to deal with this pandemic. This study aims to spatially map the vulnerability of COVID-19 based on Geographic Information Systems (GIS). The method d used is a weighted overlay. The data used are population (P), population density (PD), elderly (EP), school students (SS), and hospital beds (HB). The analysis s used is a spatial analysis using ArcGIS 10.8. The results of the study show that North Pontianak District has a very high vulnerability to COVID-19. West Pontianak District and Pontianak City have high vulnerability. South and East Pontianak sub-districts have moderate vulnerability. For Pontianak Tenggara District, the level of vulnerability to COVID-19 is very low. The vulnerability to COVID is very low in Southeast Pontianak District because it has the smallest population, low density, few elderly people, few school-age children, and lots of hospital beds. An information system is an effective tool in conveying information on the spatial distribution of the level of vulnerability of Covid-19 in an area, so that steps and handling policies can be taken according to existing priorities.